The prevalence of Staphylococcus aureus in the oral cavity of healthy adults in Malaysia - Amir Harriz Azmi; Siti Noor Adnalizawati Adnan; Normaliza Ab Malik (Penerbit Universiti Kebangsaan Malaysia, 2020)
The aim of this study was to determine the prevalence of Staphylococcus aureus in the oral cavity of healthy adults and the factors that may influence the presence of the bacteria. A cross-sectional study was conducted on a number of selected healthy adults in a district in Malaysia, during which, information about their socio-demographic background and oral hygiene practices was obtained. Oral rinse samples of the respondents were also collected using phosphate buffered saline and the data obtained was subsequently analyzed using SPSS. A total of 140 oral rinse samples were collected and the results of the analysis conducted showed a prevalence of approximately 40% of the Staphylococcus aureus in the oral cavity of the participants. There was no significant association observed between both the socio-demographic factor and oral hygiene practices with the presence of Staphylococcus aureus. The use of prostheses was found to be a significant factor for a higher prevalence of Staphylococcus aureus in the oral cavity (OR 5.13; P<0.05, 95%CI 1.410 - 18.76). The prevalence of Staphylococcus aureus in the oral cavity of healthy adults was high and the use of prostheses was a factor associated with the presence of the bacteria. This accentuates the importance of a good oral hygiene, as oral cavity can be the primary route for Staphylococcus aureus to cause potential systemic infections.